STUDIES ON GLUCOSE-LOWERING EFFICACY OF THE ACACIA SUMA ROXB. ROOT - JITENDRA DEBATA; SUNDEEP KUMAR HK (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of the study was to evaluate the glucose-lowering efficacy of the Acacia suma Roxb. (Family: Fabaceae) root extracts on Wister albino rats. Methods: A. suma roots were shade dried, powdered, and extracted by Soxhlet extraction procedure using petroleum ether, chloroform, ethanol, and water. The acute toxicity studies were conducted on Swiss albino mice as per the OECD guidelines 423. The antidiabetic activity of extracts was evaluated on adult Wistar rats at dose levels of 100,200, and 400 mg/kg P.O, respectively each using normoglycemic,glucose-loaded and Streptozotocin-induced rats. Metformin (50 mg/kg) was used as a reference standard for activity comparison. Results: Among the tested extracts, the ethanol extract was found to produce promising results that are comparable to that of the reference standard metformin. Conclusion: The study established the scientific basis for the utility of this plant in the treatment of diabetes and justifies the use of the root of the plant for treating diabetes as suggested in folklore remedies.